The influence of assisted reproductive technologies-related stressors and social support on perceived stress and depression - Aditi Gupta; Emily Lu; Zaneta Thayer (BMC, 2024)
Abstract Background While assisted reproductive technologies (ART) have helped many people experiencing infertility become pregnant, the ART process can take a psychological toll. This study examined whether and how perceived stress- and depression-related symptoms vary among individuals at different stages of the infertility and ART process, and whether ART-specific stressors and emotional support are associated with mental health symptomatology. Methods Data were collected using an online REDCap survey administered between July 2021 and March 2022. The survey was administered to 240 participants who had experienced infertility, including those who had not yet accessed ART, those undergoing ART but who were not yet pregnant, those currently pregnant through ART, and those who had given birth in the last year through ART. Each participant completed the Cohen Perceived Stress Scale (range 0-40) and the Edinburgh Depression Scale (range 0-30). Participants who had undergone ART were asked about their experience of ART-specific stressors and how helpful partner and provider support had been during the ART process. Survey data were analyzed using ANOVA and multivariate linear regressions. Results 88% of participants reported medium or high levels of perceived stress, and 43.8% of respondents showed probable indications of depression. Perceived stress and depression symptoms were significantly higher for individuals currently undergoing, but not yet pregnant from, ART treatments. These effect sizes were substantial; for example, depression scores in this group were five points higher than among currently pregnant individuals and nine points higher than among postpartum individuals. For the subset of participants who had used or were currently undergoing ART (N = 221), perceived social stigma and the physical and time demands of ART were significantly associated with higher stress and depression symptoms, while partner emotional support was associated with lower perceived stress. Conclusions The ART process exacerbates perceived stress and depression symptoms among individuals experiencing infertility. Given the potential long-term impacts on both parent and child wellbeing, clinicians and policymaking groups, including the American Society for Reproductive Medicine (ASRM), should consider making access to mental health services a standard of care during infertility treatment.